KEBIJAKAN AMERIKA SERIKAT DIBAWAH PEMERINTAHAN DONALD TRUMP DALAM MENANGGAPI PROGRAM NUKLIR KOREA UTARA - Rahayu Pertiwi; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research aims to explain foreign policy of United States under President Donald Trump toward North Korea Nuclear program. The research uses the Perspective of Conctructivism that emphasize the intersubjectivity (shared understandings) between states in their relations. The level-analysisof this research is nation-states which find that the foreign policy as manifestation of the national interest of the nation as an international actor. Theory of foreign policy that use in this research notice to explain the foreign policy as the strategy and determination in respond to international environment. This research is also supported by the concept of national identitity and interest as the measurements to act or respond which is reflected in foreign policyThe method used in this research from the measurement of the data is qualitative research method, and from the way of processing data is descriptive method. Futhermore, the technique of data analysis is based on data from literature studies with the consideration that the data is capable in providing information regarding the problem under research.The results of the research explains that the United States’ Foreign Policy under president Trump toward North Korea is based on the Strategic Accountability policy through Maximume Pressure Campaign that exert international community supports, mainly United Nations Security Council.Keyword : Foreign Policy, National Identity, National Interest, Strategic Accountability, Maximume Pressure Campaign, and Nuclear Program.